The Gendering of Global Finance - Assassi, L. author. aut Link
VII, 215 p. 1 illus.
Keywords: This book explores the gendered nature of the historical emergence of modern finance markets and their expansion to a now global scale. It analyses the ways in which women were and still are marginalized in terms of financial activity and associated structures of power which play a critical role in shaping the contemporary global political economy.